Similar increase in oxidative stress after fat overload in persons with baseline hypertriglyceridemia with or without the metabolic syndrome - Cardona, F.; Tunez, I.; Tasset, I.; Murri, M.; Tinahones, F.J. (Clinical biochemistry, 2008)
We compared the levels of biomarkers of oxidative stress before and after a fat overload in three groups. 17 controls and two groups with hypertriglyceridemia: 43 without the metabolic syndrome (TG-non-MS) and 29 with the metabolic syndrome (TG-MS). All subjects underwent a 60 g fat overload. Baseline measurements included glucose, BMI (body mass index), waist circumference and HOMA IR (homeostasis model assessment insulin resistance). Cholesterol, triglycerides, HDL (high density lipoprotein) cholesterol, TNF-alpha (tumor necrosis factor) and IL-6 (interleukin-6), lipoperoxide (LPO), carbonylated proteins, reduced glutathione (GSH), oxidized glutathione (GSSG), glutathione peroxidase (GSH-PX), glutathione reductase (GSH-Rd), catalase and glutathione transferase (GST) were measured at baseline and 3 h after fat overload. Compared to the controls, the two patient groups had higher plasma levels at baseline and after overload of cholesterol, triglycerides and apolipoprotein B, LPO, carbonylated proteins and GSSG, and lower levels of antioxidants at baseline and after the fat overload. The two patient groups had the same degree of oxidative stress.